Optimatization in Bioconversion of Quercetin Glucosides Using Aspergillus acueletus LS04-3 - Rizna Triana Dewi; Novita Ariani; Yasmin Ekapratiwi; Euis Filaila (Research Center for Chemistry - LIPI, 2021)
Microbial transformation is known to be useful for obtaining more active or less toxic compounds and achieving selective compounds conversion to more useful derivatives. The objective of this study is to explore several factors that affect the optimization of bioconversion of quercetin glucosides using Aspergillus acueletus LS04-3. To obtain the optimum condition of biotransformation the fungus was cultured under several conditions by varying the number of days of fermentation, the concentration of substrate, carbon, and nitrogen source. The transformation product was analyzed using HPLC and LCMS-MS. The results revealed that on the third-day biotransformation process, quercetin production reached the highest amount and the optimum concentration was at 50 ppm of quercetin glucoside based on HPLC analysis. In addition, from various carbon sources, glucose yielded the highest biotransformation product, while nitrogen accelerated the reaction. In this research, media of A. acueletus LS04-3 containing carbon and nitrogen could increased quercetin production. This research finding provided several factors for optimizing quercetin biotransformation by A. acueletus LS04-3. These factors were important in scaling up biotransformation even in other biotransformation reactions.